Hyperlipidemia and Its Systemic Effects: Molecular Mechanisms, Clinical Consequences, and Therapeutic Approaches: A Narrative Review - Ahmed, Firdaus Nuri; Mohammed, Hani Hadi; Mohammed, Gasha Abdalla; Rahim, Mohammed-Omer Mohammed (Journal of Sulaimani Medical College, 2025)
Background: Hyperlipidemia, marked by elevated plasma lipid and lipoprotein levels, is a significant risk factor for cardiovascular diseases linked to metabolic and endocrine disorders. Methods: This narrative review explores the pathophysiology, classification, epidemiology, systemic impact, and therapeutic approaches of hyperlipidemia. Results: Dysregulation in lipid metabolism caused by genetic mutations, insulin resistance, or lifestyle factors leads to excessive lipid accumulation and impaired clearance. Primary hyperlipidemia arises from inherited defects, including familial hypercholesterolemia and LPL deficiency, while secondary causes include diabetes, hypothyroidism, obesity, and certain medications. Hyperlipidemia is associated with significant systemic complications, including atherosclerosis, acute pancreatitis, non-alcoholic fatty liver disease, chronic kidney disease, and neurodegenerative disorders such as Alzheimer’s disease. Non-pharmacological interventions, such as dietary modification, weight loss, and exercise, remain foundational. Pharmacological agents, such as statins, fibrates, niacin, bile acid sequestrants, ezetimibe, PCSK9 inhibitors, and omega-3 fatty acids, correct lipid abnormalities and reduce the risk of cardiovascular disease. Conclusion: A comprehensive understanding of hyperlipidemia is essential for early diagnosis and effective treatment,
Keywords: Hyperlipidemia; Lipoproteins; Lipid metabolism; Dyslipidemia; Metabolic disorders